Insulin-like growth factor-1 and risk of Alzheimer dementia and brain atrophy - Westwood, Andrew J; Beiser, Alexa; Decarli, Charles; Harris, Tamara B; Chen, Tai C; He, Xue-Mei; Roubenoff, Ronenn; Pikula, Aleksandra; Au, Rhoda; Braverman, Lewis E; Wolf, Philip A; Vasan, Ramachandran S; et al. (Neurology, 2014)
To relate serum insulin-like growth factor-1 (IGF-1) to risk of Alzheimer disease (AD) dementia and to brain volumes in a dementia-free community sample spanning middle and older ages. Dementia-free Framingham participants from generation 1 (n = 789, age 79 ± 4 years, 64% women) and generation 2 (n = 2,793, age 61 ± 9 years, 55% women; total = 3,582, age 65 ± 11 years, 57% women) had serum IGF-1 measured in 1990-1994 and 1998-2001, respectively, and were followed prospectively for incident dementia and AD dementia. Brain MRI was obtained in stroke- and dementia-free survivors of both generations 1 (n = 186) and 2 (n = 1,867) during 1999-2005. Baseline IGF-1 was related to risk of incident dementia using Cox models and to total brain and hippocampal volumes using linear regression in multivariable models adjusted for age, sex, APOE ε4, plasma homocysteine, waist-hip ratio, and physical activity. Mean IGF-1 levels were 144 ± 60 μg/L in generation 1 and 114 ± 37 μg/L in generation 2. We observed 279 cases of incident dementia (230 AD dementia) over a mean follow-up of 7.4 ± 3.1 years. Persons with IGF-1 in the lowest quartile had a 51% greater risk of AD dementia (hazard ratio = 1.51, 95% confidence interval: 1.14-2.00; p = 0.004). Among persons without dementia, higher IGF-1 levels were associated with greater total brain volumes (β/SD increment in IGF-1 was 0.55 ± 0.24, p = 0.025; and 0.26 ± 0.06, p < 0.001, for generations 1 and 2, respectively). Lower serum levels of IGF-1 are associated with an increased risk of developing AD dementia and higher levels with greater brain volumes even among middle-aged community-dwelling participants free of stroke and dementia. Higher levels of IGF-1 may protect against subclinical and clinical neurodegeneration.